Dendritic zinc growth in acid electrolyte: effect of the pH - Bengoa, Leandro Nicolás (2018)
In this paper, dendritic growth at the edges of electrogalvanized steel strip has been studied using a specially designed rotating washer electrode which simulates the fluid dynamic conditions and the current density distribution at the steel strip edge found in a production line. The effect of electrolyte pH and current density on dendritic growth in an acidic zinc plating bath (ZnSO4 and H2SO4) was addressed. The temperature was kept constant at 60 °C. Solution pH was adjusted to 1, 2 or 3 using different amounts of H2SO4. In addition, the influence of temperature on the pH of the solution was determined. The current density was set at 40 or 60 A/dm2, similar to that used in the industry. Deposits were characterized using SEM and XRD. The results showed that pH strongly affects dendrites shape, length and texture. Furthermore, the morphology of dendrites at the washer edge and of deposits on the flat portion of the washer changed considerably as solution pH was increased from 1 to 3. It was found that the morphology of dendrites at the washer edge stems from the morphology of the deposit on its flat portion, which in turn determines their shape.